العنف الأسري و علاقته بالعنف المدرسي لدى عينة من المراهقين المتمدرسين بالمرحلة المتوسطة من 12-17 سنة دراسة ميدانية بمدينة الأغواط بمتوسطة سوفاري محمد بن علي - الرقطــي يمينـــة; بن صفي الدين خديجة; النوعي بدرية (My University, 2021)
The study aim to discover the relationship of the domestic violence with the school violence to the educated teenager in ( SOUFARI Mohammed ben ali middle school ) for the year 2020/2021 .determining the level of demostic violence use ( verbal and physical violence). The practiced on the adolescent and the level of school violence directed towards self and directed towards others and towards school property, in addition to revealing the differences in the degree of exposure of schoolchildren in the middle school to domestic violence according to the variable of gender, age variable and academic level, and we have relied in this study on the descriptive correlative approach ,The basic sample consisted of 112 male and female students, of whom (65) females and (47) males were distributed at four levels of the first, second, third and fourth year average, and their ages ranged from (12 to 17 years). The stratified sample was chosen in a simple random way, and it was applied The domestic violence questionnaire and the school violence questionnaire after verifying the psychometric properties of these tools. The statistical methods were used, the arithmetic mean, standard deviation, Pearson correlation coefficient, Crombach's alpha coefficient, one-way variance test and (t) test.The results indicated that there was a positive correlation between domestic violence and school violence, with a statistical significance of (0.68). The results of the study also showed a decrease in the level of domestic violence and school violence among school-aged adolescents in middle school. Also, there were statistically significant differences in the degree of domestic violence and the degree of school violence directed at school-aged adolescents due to gender and age variables In the end , we concluded from the study that , despite of the existence of this relationship between the violence domestic and violence of school , that ‌ adolescence factor has an influence on the student's practice of school violence